2017
DOI: 10.1016/j.acra.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

CT for Acute Nontraumatic Abdominal Pain—Is Oral Contrast Really Required?

Abstract: Our study shows that oral contrast is noncontributory to radiological diagnosis in most patients presenting to the ED with acute nontraumatic abdominal pain. These patients can therefore undergo abdominal CT scanning without oral contrast, with no effect on radiological diagnostic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 24 publications
2
19
0
3
Order By: Relevance
“…Use of Oral and Rectal Contrast Media for CT. A retrospective review of 661 patients found no significant difference in the ability to correctly diagnose a suspected acute abdominal process (including 199 cases of infectious/inflammatory findings) when CT imaging with oral contrast was compared with CT imaging performed without oral contrast [27]. Another study of 348 consecutive patients who presented to the emergency department for nontraumatic abdominal pain found no significant diagnostic benefit of oral contrast [28]. Although oral contrast practices for abdominal and pelvic CT vary nationally, rectal contrast is rarely used [29].…”
Section: Special Imaging Considerationsmentioning
confidence: 99%
“…Use of Oral and Rectal Contrast Media for CT. A retrospective review of 661 patients found no significant difference in the ability to correctly diagnose a suspected acute abdominal process (including 199 cases of infectious/inflammatory findings) when CT imaging with oral contrast was compared with CT imaging performed without oral contrast [27]. Another study of 348 consecutive patients who presented to the emergency department for nontraumatic abdominal pain found no significant diagnostic benefit of oral contrast [28]. Although oral contrast practices for abdominal and pelvic CT vary nationally, rectal contrast is rarely used [29].…”
Section: Special Imaging Considerationsmentioning
confidence: 99%
“…To the best of our knowledge, no study has compared CT with and without rectal contrast specifically for the clinical workup of DD. A few studies have compared the value of CT with and without rectal/enteric contrast in patients with appendicitis [21] and in patients with acute non-traumatic pain [22], concluding that enteric contrast does not improve the radiological diagnosis in most patients [23]. The diagnostic accuracy (94.8 %), sensitivity (91.7 %), and specificity (97.3 %) of CT with i. v. contrast alone in our study are comparable with previous studies in patients with DD who underwent CT with varying enteric contrast protocols.…”
Section: Discussionmentioning
confidence: 99%
“…CT protocol in patients with suspected bowel obstruction has been studied for years. It is well known that the oral administration of a high-attenuation contrast agent is no longer recommended for this diagnosis [7]. While there is a consensus on contrast-enhanced CT as the first-line examination for abdominal emergencies, the value of unenhanced CT - that is yet performed in many institutions - is more controversial [2, 3, 8–13].…”
Section: Introductionmentioning
confidence: 99%